2006
DOI: 10.4141/p05-016
|View full text |Cite
|
Sign up to set email alerts
|

Cultivar-specific management for seed production of creeping red fescue

Abstract: Fairey, N. A. 2006. Cultivar-specific management for seed production of creeping red fescue. Can. J. Plant Sci. 86: 1099-1105. A study was conducted in the Peace River region of north-western Canada with three cultivars (Boreal, Jasper, Jasper E) of creeping red fescue (Festuca rubra L. var. rubra) to identify cultivar-specific management practices for seed production. Experimental treatments included four methods of establishment [Broadcast; 30-cm rows; 15-cm rows; 15-cm rows with sulfur (56 kg ha -1 SulFer 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
2
4
1
Order By: Relevance
“…Fertile tiller density in the first year was increased by N, regardless of the rate of N applied and, when all the N was applied to the first seed crop, fertile tiller density was almost as high in the second seed crop as it was when all the N had been applied directly to the second seed crop (Table 2). The increase in fertile tiller density by N application agrees with numerous reports (Nordestgaard 1980;Cedell 1986;Rolston et al 1997;Fairey and Lefkovitch 2000;Fairey 2006). Harvest index of the first seed crop was higher for the zero'102 N treatment (51.4%) than for any of the other N treatments (37.3 to 40.2%) (Table 3), the higher value indicating that the plants were diverting assimilates to support the growth of seed rather than vegetative tissues.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Fertile tiller density in the first year was increased by N, regardless of the rate of N applied and, when all the N was applied to the first seed crop, fertile tiller density was almost as high in the second seed crop as it was when all the N had been applied directly to the second seed crop (Table 2). The increase in fertile tiller density by N application agrees with numerous reports (Nordestgaard 1980;Cedell 1986;Rolston et al 1997;Fairey and Lefkovitch 2000;Fairey 2006). Harvest index of the first seed crop was higher for the zero'102 N treatment (51.4%) than for any of the other N treatments (37.3 to 40.2%) (Table 3), the higher value indicating that the plants were diverting assimilates to support the growth of seed rather than vegetative tissues.…”
Section: Resultssupporting
confidence: 91%
“…The present results confirm the existence of an optimum amount of N for seed yield of red fescue as found by others (Nordestgaard 1980;Rolston et al 1997;Fairey 2006), but also shows, for the study region, that the prevailing moisture environment influences the effectiveness of N utilization for the realisation of seed yield. The differences observed in seed yield do not appear to be related to the mass of root organic matter as, despite the diverse nature of the 24 experimental treatments, there were no significant differences (P 0 0.05) among the treatments in the mass of root organic matter recovered from the fescue plants after the harvest of the second seed crop; on average, the mass of root organic matter was 642 g m (2 (Table 6).…”
Section: Kg Hasupporting
confidence: 92%
See 2 more Smart Citations
“…It was also shown that seed yield was the greatest when N was applied at doubleridge stage (BBCH 30-31). According to Fairey [39] in order to maximize the yield from two years of full production of Festuca rubra var. rubra, a rate of 55 to 80 kg N ha −1 is sufficient, to be applied each time during the fall prior to the harvest year.…”
Section: Discussionmentioning
confidence: 99%